2013
DOI: 10.1093/jrr/rrt128
|View full text |Cite
|
Sign up to set email alerts
|

High-dose-rate brachytherapy and hypofractionated external beam radiotherapy combined with long-term hormonal therapy for high-risk and very high-risk prostate cancer: outcomes after 5-year follow-up

Abstract: The purpose of this study was to report the outcomes of high-dose-rate (HDR) brachytherapy and hypofractionated external beam radiotherapy (EBRT) combined with long-term androgen deprivation therapy (ADT) for National Comprehensive Cancer Network (NCCN) criteria-defined high-risk (HR) and very high-risk (VHR) prostate cancer. Data from 178 HR (n = 96, 54%) and VHR (n = 82, 46%) prostate cancer patients who underwent 192Ir-HDR brachytherapy and hypofractionated EBRT with long-term ADT between 2003 and 2008 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
(25 reference statements)
0
27
1
Order By: Relevance
“…It has been reported that the combination of ADT with RT improves results of high-risk PCa treatment [29]. In our multivariate meta-regression analysis, we found that the reported percent of patients on ADT was not associated with urethral strictures.…”
Section: Discussionmentioning
confidence: 45%
“…It has been reported that the combination of ADT with RT improves results of high-risk PCa treatment [29]. In our multivariate meta-regression analysis, we found that the reported percent of patients on ADT was not associated with urethral strictures.…”
Section: Discussionmentioning
confidence: 45%
“…The 5-year biochemical control and overall survival rates were 90.6% (HR 97.8%, VHR 81.9%) and 96.9% (HR 100%, VHR 93.3%), respectively. 18 In a multivariate analysis that examined the independent contribution of each component of the VHR criteria with oncological outcomes, primary Gleason pattern 5 was associated with increased risks of BF and DM. Increasing evidence has suggested that, among HR groups, Gleason score 9-10 disease defines a particularly aggressive natural history with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additional needles were placed into the base of the seminal vesicles in all clinical stages. The average number of needles implanted was 17 (range [12][13][14][15][16][17][18]. In the longitudinal section, the tip of the needle was advanced within the bladder lumen with the aim of preventing the interfractional displacement of implant needles in the caudal direction, which was caused by edema and/or hematoma of the prostate, periprostatic and perineal tissues (Fig.…”
Section: Hdrbtmentioning
confidence: 99%
“…Low-dose-rate (LDR) brachytherapy provides superior outcomes in patients with low-and intermediate-risk diseases [1,2]. The combination of high-dose-rate (HDR) brachytherapy and external irradiation is an effective treatment for delivering radiation doses more precisely in prostate cancer, even if patients have extracapsular invasion and seminal vesicle invasion [3][4][5]. Technical modifications for prostate brachytherapy are being developed to obtain the better treatment outcome [2,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Technical modifications for prostate brachytherapy are being developed to obtain the better treatment outcome [2,[7][8][9][10]. However, approximately 5%-20% of those patients, as it now stands, show recurrence within 5 years after brachytherapy [1,2,5,11,12].…”
Section: Introductionmentioning
confidence: 99%